Evolution of fundamental mechanical properties with aliovalent Co/Cu partial substitution and preparation method for Y-123 system - Ozturk, O.; Safran, S.; Ada, H.; Bulut, F.; Seydioglu, T.; Nefrow, A. R. A.; Akkurt, B.; Terzioglu, C.; Yildirim, G. (Springer Science and Business Media LLC, 2024)
AbstractThis study investigates the effect of aliovalent Co/Cu replacement and preparation method on fundamental mechanical performance features of YBa2Cu3−xCoxO7−δ (Y-123) ceramic system depending on the crack propagation mechanism by Vickers hardness measurements (Hv) and mechanical investigation models for the first time. All the findings are verified by the scanning electron microscopy (SEM) examinations. Besides, the electron-dispersive X-ray (EDX) technique verifies the successful substitution mechanism. Besides, the Vickers hardness parameters improve systematically with the increment in the Co/Cu partial substitution (serving as a barrier) level due to formation of operable slip systems, ionic bond formations, and decrement of stress-amplified strain fields. Moreover, the Y-123 ceramic produced by solid-state reaction method and molecular weight of 0.20% presents the densest and smoothest surface morphology with the largest particle distributions and well-linked cobblestone-like grains. On the other hand, the Y-123 ceramic compounds produced by the sol–gel method are more sensitive and responsive to the indentation test loads. All the findings are wholly supported by the mechanical performance properties, including the shear modulus, resilience, and degree of granularity. Furthermore, the mechanical models indicate that every compound prepared exhibits the untypical reverse indentation size effect (RISE). Additionally, the modeling studies display that the induced cracking (IIC) approach is found to be the most appropriate method to examine true Vickers hardness parameters in the plateau limit regions. All in all, this comprehensive study reports efficiently exploiting the process–structure–property relationships in Y-123 ceramic material design for physical science and mechanical application fields using the aliovalent partial substitution and preparation condition.
Keywords: Densest; Ceramics; Superconducting Properties; Growth; X-ray; Mechanical Performance; Microhardness; Process-Structure; Partial Substitution; Smoothest; Cu